Improving the Existence of Labuhan Lombok Tourism Destinations Through Website-Based Tourism Information Systems - Abdul Wafa; Nadiyasari Agitha; Isaque Manteiga Joaquim (English and Tourism Studies, 2025)
Labuhan Lombok has plentiful natural tourism potential and a strategic location near Kayangan Harbor, yet its popularity remains relatively low. The use of internet technology, particularly web-based information systems, has been increasingly utilized to promote tourism destinations. This study aims to enhance the prominence of Labuhan Lombok as a tourism destination through the development of a web-based information system. The system was developed using the waterfall method, which includes the stages of requirements analysis, design, implementation, testing, and deployment. Additionally, testing was conducted using User Acceptance Testing (UAT) to ensure the system meets user needs. The developed system provides a comprehensive information platform featuring tourist destinations, events, culinary options, and souvenirs. The results of the UAT showed that the information system is considered effective in promoting Labuhan Lombok as a tourism destination. Thes system is designed with a user-friendly interface that supports sustainable tourism promotion without harming expected to enhance the appeal of Labuhan Lombok, support tourism promotion, and contribute to the growth of the local tourism sector.